PENGARUH RETURN ON EQUITY (ROE), CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM - Sugandi, Samitha Serly; Kasir, Kasir (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the effect of Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER) on the stock price of companies in the property and real estate subsector listed on the Indonesia Stock Exchange (IDX) during the period 2016–2024. The research method used is quantitative with a descriptive and verification approach, as well as multiple linear regression analysis techniques. Secondary data were obtained from the company's annual report published on the official IDX website. The research sample consisted of 63 company observations that met the purposive sampling criteria. The results showed that ROE had a significant positive effect on stock prices, while CR and DER had a significant negative effect. The coefficient of determination (R²) of 56.3% indicates that the combination of the three independent variables can explain most of the variation in stock prices, while the rest is influenced by other factors outside this model. Keywords: Return On Equity (ROE), Current Ratio (CR), Debt to Equity Ratio(DER), Stock Prices.